ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2016å±Šå¦ç”Ÿå¯¹æ—¶é—´å‰¯è¯â€œæ£â€ã€â€œåœ¨â€ ä¸Žâ€œæ£åœ¨â€çš„æŽŒæ¡æƒ…å†µåˆ†æž - Rianti, Novi; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractÂ Adverbs is an important part in Mandarin grammar. â€œZhengâ€ , â€œZaiâ€ and â€œZheng Zaiâ€ are include as adverb of time. These three words are often use in daily life. Can be seen from the word the meaning of the words and the usage , there are similarities and differences. Therefore, students who learn Mandarin in process learning of these three words often make mistakes in understanding which is can create a misuse the words.To find out how the mastery codition of student from Mandarin education study program of FKIP UNTAN batch 2016 toward the adverb time words which are â€œZhengâ€ , â€œZaiâ€ , and â€œZheng zaiâ€ , the writer use research test method to know the mastery condition of students and analyze student difficulties toward those three words. The result shows that the mastery condition of students toward â€œZheng Zaiâ€ are very good, the true percentage are above 70% and the mastery condition toward â€œZhengâ€ and â€œzaiâ€ are not that good, which the percentage only below 60% . In the analysis of the type of difficulty, the writer found the mistakes that often occurs is the mistakes in choosing the words.Keywords : Adverb, Zheng, Zai, Zheng Zai. Mastery Condition